Measurements with an atomic force microscope using a long travel nanopositioning and nanomeasuring machine - Hofmann, Norbert; Hausotte, Tino; Jäger, Gerd; Manske, Eberhard (4th IEEE Conference on Nanotechnology, 2004)
A nanopositioning and -measuring machine (NMM) was developed at the Institute of Measurement and Sensor Technology. It offers a movement range of 25 mm x 25 mm x 5 mm with a resolution of 0.1 nm. To use the NMM as an instrument to measure micro- and nanostructures on small objects a commercial atomic force microscope (AFM) was integrated. A ULTRAObjective standard by Surface Imaging Systems Germany was used for this. Extensive measurements were carried out to test the metrological characteristics of the system. Different measuring modes showed a big influence on the achieved results.
Keywords: AFM; calibration; nanopositioning; nanometrology; precision measurement